National Conference on Unearth the New Frontiers in Life Sciences: Life Sciences-Enzymes - S. Malarvizhi, CHIEF PATRON (International Journal of Life Science and Pharma Research, 2019)
As the Quote goes though the garment industry and recent technologies has created enormous opportunities even beyond what nature can offer but the damage and the impact it creates to the environment is beyond the acceptable level. The damage it causes starts right from the farming of cotton till the final finishing and processing of fabric. The industry use different harmful chemicals in various processes like, desizing, scouring, bleaching, mercerizing, dyeing, washing, finishing, and it utilizes large quantities of water and also large amount of waste waters in each stages of processing Biotechnology is the process of applying living organisms and their different components for industrial processes and products. In the current scenario the application of biotechnology is wide.